Idx184 in Combination with Pegylated Interferon-α2A and Ribavirin for 2 Weeks in Treatment-Naive Patients with Chronic Hepatitis C. Issue 6 (August 2013) - Lalezari, Jacob; Box, Terry; O'Riordan, William; Mehra, Purvi; Nguyen, Tuan; Poordad, Fred; DeJesus, Edwin; Kwo, Paul; Godofsky, Eliot; Lawrence, Shannon; Dubuc-Patrick, Gloria; Chen, Jie; et al.
Background: IDX184 is a liver-targeted nucleotide prodrug that selectively inhibits HCV NS5B polymerase. Methods: This randomized, double-blind, placebo-controlled, ascending-dose study investigated the antiviral activity, safety and pharmacokinetics of IDX184 plus pegylated interferon-α2a and ribavirin (P/R) in treatment-naive patients with genotype-1 HCV. A total of 81 patients with baseline HCV RNA≥5 log10 IU/ml, alanine aminotransferase ≤3 xupper limit of normal and compensated liver disease were dosed. Sequential cohorts of 20 patients, randomized 16:4 (active:placebo), received IDX184 for 14 days at rising daily doses of 50, 100, 150 or 200 mg in combination with P/R for 14 days. Results: At the end of triple dosing, HCV RNA changes from baseline (mean ±sd log10 ) and proportion of patients achieving undetectable viral load (<15 IU/ml) based on the efficacy-evaluable population were -2.7 ±1.3 (13%), -4.0 ±1.7 (50%), -4.2 ±1.9 (50%), -4.1 ±1.2 (40%), -4.3 ±1.5 (29%) and -3.7 ±1.2 (25%) for the 50 mg once daily, 50 mg twice daily, 100 mg once daily, 150 mg once daily, 100 mg twice daily and 200 mg once daily IDX184 doses, respectively. P/R alone resulted in a reduction of -1.5 ±1.3 log10 with only 6% of patients with undetectable viral load. Patients with genotypes-1a or -1b responded similarly. No viral breakthrough or resistance associated with IDX184 was observed. Anti-HCV activity of IDX184 correlated with plasma exposure of its nucleoside metabolite 2′-methylguanosine. Most adverse events were mild or moderate in severity and were consistent with those associated with P/R. The most common adverse events were fatigue and headache. Conclusions: IDX184 in combination with P/R for 14 days was well tolerated and demonstrated greater antiviral activity with more patients achieving undetectable viral load than P/R.